Measuring water use, conservation, and differences by gender using an inexpensive, high frequency metering system. (October 2017) - Horsburgh, Jeffery S.; Leonardo, Miguel E.; Abdallah, Adel M.; Rosenberg, David E.
Abstract: We present an inexpensive, open source, water metering system for measuring water use quantity and behavior at high temporal frequency. We demonstrate this technology in two high-traffic, public restrooms at Utah State University before and after installing high efficiency, automatic faucets and toilet flush valves. We also integrated an inexpensive sensor to count user traffic. Sensing restroom visits and water use events allowed us to identify fixture malfunctions, average water use per person, variability in use by fixtures (faucets versus urinals and toilets), variability in use by fixtures compared to manufacturer specifications, gender differences in use, and the difference in use after retrofit of the restrooms with high efficiency fixtures. The inexpensive metering system can help institutions remotely measure and record water use trends and behavior, identify leaks and fixture malfunctions, and schedule fixture maintenance or upgrades, all of which can ultimately help them meet goals for sustainable water use. Highlights: We present an inexpensive, open source, water metering system. We measured water use quantity and behavior at high frequency in public restrooms. We examined variability in use across genders for faucets, toilets, and urinals. Results show modified water use after installing high efficiency fixtures. High frequency data can help water managers meet goals for sustainable water use.